The Influence of Digital Literacy and Education Level on E-Government Utilization by Village Officials in Desa Cinta Statistik (Desa Cantik) Program, Wonogiri Regency - Vika Nafesia; Ahmad Yusroni (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study aims to analyze and examine the influence of digital literacy and educational level, both partially and simultaneously, on the utilization of e-government by village officials in three villages participating in the Desa Cinta Statistik (Desa Cantik) Program, namely Kepatihan, Keloran, and Wonoharjo Villages, Wonogiri Regency. This study employed a quantitative associative approach using purposive sampling to determine the research locations and saturated sampling to select the respondents, resulting in a total of 70 respondents. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS software. The findings reveal that digital literacy has a significant positive effect on the utilization of e-government, whereas educational level does not have a significant partial effect. However, the two variables simultaneously have a significant effect on the utilization of e-government, explaining 61.5% of the variance. These findings indicate that strengthening the digital literacy competencies of village officials plays a more decisive role in the successful implementation of the Village Information System than formal educational attainment alone. Therefore, strategies to enhance the capacity of village government personnel should prioritize continuous technical training and digital mentoring programs.